Analysis of Market Competition and Customer Loyalty in the Business Feasibility Study of UD Putra Jati in Kasiman District, Bojonegoro - Aisha Nurrahma Naifa; Abdur Rohman (ORGANIZE: Journal of Economics, Management and Finance, 2025)
This study aims to analyze market competition conditions and factors that influence customer loyalty at UD Putra Jati, a small and medium enterprise (SME) engaged in the production and sale of teak wood crafts in Kasiman District, Bojonegoro. This study uses a qualitative approach with a descriptive method. Data collection techniques are carried out through direct observation and in-depth interviews with owners and customers. The results of the study indicate that the COVID-19 pandemic has had a significant impact on declining sales and changes in consumer behavior. UD Putra Jati faces challenges in the form of suboptimal use of digital marketing, limited production capacity, and the absence of complete business legality. However, product quality and customer loyalty remain the main strengths of this business. This study recommends innovative strategies in the form of production modernization, utilization of social media, business legalization, and development of online distribution and marketing systems. These findings are expected to be a reference for other SMEs in developing adaptive strategies to face market dynamics and increase business competitiveness sustainably.